2017
DOI: 10.1134/s0012496617050064
|View full text |Cite
|
Sign up to set email alerts
|

Recent decrease in carbon sink to Russian forests

Abstract: Regional Evaluation of Carbon Budget of Forests (RECBF), was used to study the dynamics of carbon balance in Russian forests in 1988-2015. The carbon sink (excess of absorption over losses) to forests was minimal in 1988. Since the first half of the 1990s, its increase has started. This increase was associated with the reduction of logging volume in connection with socioeconomic reforms. Since 2008, the carbon sink was gradually reduced due to increasing losses in logging operations, forest fires, and decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…As in GCASv1 (Zhang et al, 2015), the Model for OZone And Related chemical Tracers, version 4 (MOZART-4; Emmons et al, 2010) is adopted as the atmospheric transport model in GCASv2. MOZART-4 is a flexible model, can be run at essentially any resolution, and can be driven by essentially any meteorological data set and with any emission inventory (Emmons et al, 2010).…”
Section: Atmospheric Transport Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…As in GCASv1 (Zhang et al, 2015), the Model for OZone And Related chemical Tracers, version 4 (MOZART-4; Emmons et al, 2010) is adopted as the atmospheric transport model in GCASv2. MOZART-4 is a flexible model, can be run at essentially any resolution, and can be driven by essentially any meteorological data set and with any emission inventory (Emmons et al, 2010).…”
Section: Atmospheric Transport Modelmentioning
confidence: 99%
“…To avoid the influence of spurious signals, Kang et al (2012) used a very short DA window (6 h) in their assimilation system (LETKF_C) and pointed out that the flux inversion with a long window (3 weeks) is not as accurate as that obtained with a 6 h DA window, particularly in smaller-scale structures. During the development of GCASv1, Zhang et al (2015) tested different DA windows and found that the longer the window, the larger the optimized terrestrial carbon sink, resulting in a smaller optimized annual atmospheric CO 2 growth rate (AGR) compared with the observed rate. Considering the fact that, due to the release of satellite XCO 2 retrievals like GOSAT and Orbiting Carbon Observatory-2 (OCO-2), the atmospheric CO 2 observations and coverage have increased significantly compared with what was available in the past, we no longer need to extend the DA window to include more observational data.…”
Section: Da Window and Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…China's surface in situ CO 2 measurements [75]. In boreal lands, our estimated sinks are stronger than previous studies, especially in boreal Asia, where previous studies showed a moderate sink in the range of -0.11 to -0.76 PgC yr -1 [70,[76][77][78][79]. In tropical and southern lands, the inverted NEE in S. America, Australia, and tropical Asia are roughly close to those from previous studies [70], but the inverted NEE in Africa has a great difference from previous studies.…”
Section: Journal Of Remote Sensingmentioning
confidence: 65%
“…(2019) applied the prior flux from CT2016 to optimizing the fluxes in 2015, and they showed a similar distribution of land sinks over tropical lands to that of CT2017. In Boreal Asia, the land sink estimated by bottom-up approaches was in the range of -0.11 ~ -0.76 PgC yr −1 (Hayes et al, 2011;Nilsson et al, 2003;Dolman et al, 2012;Zamolodchikov et al, 2017). CarbonTracker usually reports a very stronger carbon sink (Jacobson et al 2020;Peter et al, 2007;Zhang et al, 2014), one possible reason is that there are no enough surface observations in Asia boreal regions.…”
Section: Regional Carbon Fluxmentioning
confidence: 99%